SUMBANGSIH MUHAMMADIYAH DALAM MELURUSKAN PANDANGAN YANG KELIRU TERHADAP PEMAKNAAN MACCERA’ BINANGA DI BULUKUMBA - Mahmuddin, Mahmuddin (Jurnal Dakwah Tabligh, 2018)
This journal is to present about the contribution of Muhammadiyah in getting back the points of Maccera’ binanga in Bulukumba. Therefore, this journal is intended to talk about the action of Maccera’ binanga and Muhammadiyah’s contribution in correcting point of viewof Maccera’ Binanga which is still fallacious in Bulukumba. The collecting data done by indepth interview which is, then, examined through dakwah theory and social change theory. The outcome of this research points out that point of view of Bulukumbanesse about Maccera’ binanga is as an inscription to the Sea God for the fish. This thing must be done as if it is not done, so the God will be indignant and there is no more fish for the coming year. The Maccera’ binanga is usually done along with animal slaughter in the river springhead, and then the animal’s head is throw away in to the sea with sokko’ (A rice made from sticky rice), grilled chicken which is put in Suji ball. The fishermen have a point that Maccera’ binanga is a ritual which must be done every year.